ChemInform Abstract: A Highly Diastereoselective Five‐Component Synthesis of 1‐(Alkylimino)‐5, 5‐dicyano‐3a‐aryloctahydro‐3‐oxacyclobuta [cd]pentalene‐1a, 2, 5a, 5b(2H, 3aH)‐tetracarboxylates. Issue 7 (29th January 2015) - Adib, Mehdi; Sheikhi, Ehsan; Haghshenas, Pouyan; Rajai‐Daryasarei, Saideh; Bijanzadeh, Hamid Reza; Zhu, Long‐Guan
Abstract The novel 1:1:1:2 addition reaction of phenacyl bromide, malononitrile, isocyanide, and acetylenedicarboxylate provides the polycyclic product (V) as the only one of 16 possible diastereomers.